Factors affecting achievement of glycemic targets among type 2 diabetes patients in South Asia: Analysis of the CARRS trial. (January 2021) - Masood, Muhammad Q.; Singh, Kavita; Kondal, Dimple; Ali, Mohammed K.; Mawani, Minaz; Devarajan, Raji; Menon, Usha; Varthakavi, Premlata; Viswanathan, Vijay; Dharmalingam, Mala; Bantwal, Ganapathi; Sahay, Rakesh; et al.
Abstract: Objective: To assess the predictors of achieving and maintaining guideline-recommended glycemic control in people with poorly controlled type 2 diabetes. Methods: We analyzed data from the Centre for Cardiometabolic Risk Reduction in South Asia (CARRS) Trial (n = 1146), to identify groups that achieved guideline-recommended glycemic control (HbA1c < 7%) and those that remained persistently poorly controlled (HbA1c > 9%) over a median of 28 months of follow-up. We used generalized estimation equations (GEE) analysis for each outcome i.e. achieving guideline-recommended control and persistently poorly controlled and constructed four regression models (demographics, disease-related, self-care, and other risk factors) separately to identify predictors of HbA1c < 7% and HbA1c > 9% at the end of the trial, adjusting for trial group assignment and site. Results: In the final multivariate model, adherence to prescribed medications (RR: 1.46, 95%CI: 1.09, 1.95), adherence to diet plans (RR: 1.79, 95% CI: 1.43, 2.23) and middle-aged: 50–64 years (RR: 1.32; 95% CI: 1.02–1.71) were associated with achieving guideline-recommended control (HbA1c < 7%). Presence of microvascular complications (RR: 0.70; 95%CI: 0.53–0.92) reduced the probability of achieving guideline-recommended glycemic control (HbA1c 7%). Further, longer duration of diabetes (>15 years), RR: 1.41; 95% CI: 1.15, 1.72, hyperlipidemia, RR: 1.19; 95% CI: 1.06, 1.34 and younger age group (35–49 years vs. >64 years: RR: 0.61; 95% CI: 0.47–0.79) were associated with persistently poor glycemic control (HbA1c > 9%). Conclusion: To achieve and maintain guideline-recommended glycemic control, care delivery models must put additional emphasis and effort on patients with longer disease duration, younger people and those having microvascular complications and hyperlipidemia.